Evaluation of Borama tuberculosis control program in Somaliland, Somalia - Mohamed Gedi Qayad; Gianfranco Tarsitani (Journal of Infection in Developing Countries)
Introduction: The Borama TB program in Somalia lost resources for TB operations in 2003. We evaluated the impact of the loss on the program. Methodology: Pre-event (2002–2003) and post-event (2007) design were used. All TB patients registered in Borama and a sample of four months from Hargeisa (comparison) TB patients in both periods were abstracted. The following TB treatment outcomes were estimated: treatment success, treatment failure, case fatality, treatment interruption and transfer rates, along with percentage of patients with sputum specimen prior to treatment, percentage of patients from neighboring countries, and monthly average patients enrolled in treatment. The pre-event to post-event outcomes and measures were compared using descriptive and multivariate analyses. Results: In total, 3,367 TB cases were abstracted. In Borama, the TB treatment success rate increased 6% in the post-event. The treatment failure and interruption rates both declined 75%. Monthly average TB patients declined 55%. Percentage of patients smear tested prior to the initiation of the treatment declined 9%. Percentage of TB patients from neighboring countries and other parts of Somalia declined 51%. Treatment interruption/transfer rates declined significantly in the post-event, compared to the pre-event period. Treatment failure/death rate did not change in the post-event period. In Hargeisa, the treatment success, failure/death, and interruption/transfer rates were similar in both periods. The RR did not change in these measures after adjusting for age and gender. Conclusions: This study indicates a significant setback to the Borama TB control program in the majority of measures evaluated, except the TB success rate.